2017
DOI: 10.1016/j.fcr.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of diammonium phosphate use in bush and climbing bean-maize rotations in smallholder farms of Central Burundi

Abstract: A B S T R A C TSoil fertility decline is a major constraint to bean (Phaseolus vulgaris L.) and maize (Zea mays) production in the Central Highlands of Burundi. Nutrient sources, specifically fertilizers, are paramount to increasing the production in the regions. Hence, improving fertilizer use efficiency is considered as a key factor towards sustainable intensification. The use of grain legumes with low harvest indices, such as climbing beans, are assumed to improve soil fertility and fertilizer use efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…A recent review of MVCR estimates for maize plots in Africa indicates that fertilizer use is either unprofitable or only marginally profitable in many contexts . Similar studies on profitability of fertilizer application on maize farms arrive at similar conclusions for farms in Benin (Tovihoudji 2018), Burkina Faso (Theriault, Smale, and Haider 2018), Burundi (Niyuhire et al 2017), Ethiopia (Rashid et al 2013), Ghana (Ragasa and Chapoto 2017), Nigeria (Liverpool-Tasie 2017), Tanzania (Mather et al 2016), and Zambia (Burke, Thom, and Black 2017). Factors correlated with returns to fertilizer use include agroecological context and production systems (for example, irrigated versus rainfed, high-potential versus fragile production zones) and soil characteristics (for example, soil pH levels).…”
Section: The Returns To Fertilizer Usesupporting
confidence: 59%
“…A recent review of MVCR estimates for maize plots in Africa indicates that fertilizer use is either unprofitable or only marginally profitable in many contexts . Similar studies on profitability of fertilizer application on maize farms arrive at similar conclusions for farms in Benin (Tovihoudji 2018), Burkina Faso (Theriault, Smale, and Haider 2018), Burundi (Niyuhire et al 2017), Ethiopia (Rashid et al 2013), Ghana (Ragasa and Chapoto 2017), Nigeria (Liverpool-Tasie 2017), Tanzania (Mather et al 2016), and Zambia (Burke, Thom, and Black 2017). Factors correlated with returns to fertilizer use include agroecological context and production systems (for example, irrigated versus rainfed, high-potential versus fragile production zones) and soil characteristics (for example, soil pH levels).…”
Section: The Returns To Fertilizer Usesupporting
confidence: 59%
“…The differences in yields observed could be linked to differences in past management practices among the participating farmers. Increased yield of climbing bean when organic and inorganic fertilizers are combined has been reported elsewhere (Niyuhire et al, 2017). Manure is reported to increase the crop yield and responses to applied fertilizers (Rurangwa et al, 2018), and past manure application was identified as the most factor affecting yields and yields response to applied fertilizers (Njoroge et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…The indeterminate growth of climbing beans allows them to provide a continuous supply of green leaves and pods as well as dry grain throughout the growing season (Sperling and Muyaneza, 1995;Wortmann et al, 2001). Strong residual effects have been reported when maize is grown after climbing bean, which are attributed to the large amounts of above-and belowground crop residues (Niyuhire et al, 2017), changes in microbial activities (Turco et al, 1990), and access to more P (Bainville et al, 2005). Climbing beans also provide valuable residues for livestock feed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also indicated that other rotational benefits are derived from the improvement of soil properties and increase in mycorrhizal infection as well as shielding against disease and pests to the subsequent maize crop (Argaw et al, 2015;Gan et al, 2015;Munishi et al, 2015). The findings of the present study are also consistent with studies conducted elsewhere (Wahbi et al, 2016;Niyuhire et al, 2017). Kamanga (2002) pointed that the subsequent cereal crop utilizes at least 50% of the N returned to the soil through the incorporation of dead and decomposed legume residues over the growing season.…”
Section: Productivity Of Maize and Common Bean Rotations Over Five Cr...supporting
confidence: 90%